2018
DOI: 10.1038/s41598-018-31890-9
|View full text |Cite
|
Sign up to set email alerts
|

Geobiology reveals how human kidney stones dissolve in vivo

Abstract: More than 10% of the global human population is now afflicted with kidney stones, which are commonly associated with other significant health problems including diabetes, hypertension and obesity. Nearly 70% of these stones are primarily composed of calcium oxalate, a mineral previously assumed to be effectively insoluble within the kidney. This has limited currently available treatment options to painful passage and/or invasive surgical procedures. We analyze kidney stone thin sections with a combination of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 43 publications
4
76
0
Order By: Relevance
“…Super-resolution microscopy of etched skeletal wall thin sections less than 10 µm-thick reveals for the first time in modern corals that Porites sclerodermites are composed of 140 nm-thick couplets of dark and light layering (Figure 12). These are similar to those observed in human calcium oxalate kidney stones (Sivaguru et al, 2018a) and are consistent with 10-40 nm-thick dark-light layering observed in fossil Triassic-age coral sclerodermites under focused ion beam microscopy (Frankowiak et al, 2013). Sclerodermite layers 2-3 µm in thickness have previously been interpreted to be the result of daily deposition (Cohen and McConnaughey, 2003).…”
Section: Original Hdb and Ldb Skeletal Structuresupporting
confidence: 86%
See 2 more Smart Citations
“…Super-resolution microscopy of etched skeletal wall thin sections less than 10 µm-thick reveals for the first time in modern corals that Porites sclerodermites are composed of 140 nm-thick couplets of dark and light layering (Figure 12). These are similar to those observed in human calcium oxalate kidney stones (Sivaguru et al, 2018a) and are consistent with 10-40 nm-thick dark-light layering observed in fossil Triassic-age coral sclerodermites under focused ion beam microscopy (Frankowiak et al, 2013). Sclerodermite layers 2-3 µm in thickness have previously been interpreted to be the result of daily deposition (Cohen and McConnaughey, 2003).…”
Section: Original Hdb and Ldb Skeletal Structuresupporting
confidence: 86%
“…A suite of integrated optical microscopy techniques were applied to determine the crystalline structure of the Porites coral skeletal cores in thin section. This included the first integrated application to coral skeletons of the suite of Airyscan super-resolution auto-fluorescence microscopy (SRAF), bright field (BF), dark field (DF), polarization (POL), phasecontrast (PC), and ring aperture contrast (RAC) techniques (Sivaguru et al, 2012(Sivaguru et al, , 2018a. XRD and MicroCT digital transparencies were directly overlaid on images collected from each of these modalities for each thin section to determine the precise position of HDBs and LDBs, and conduct optical microscopy (140-250 nm-resolution) within the context of the CSDB stratigraphic sequences.…”
Section: Optical Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Although diffraction limit is surpassed in fluorescence imaging (Sheppard, ; Hell & Wichmann, ; Gustafsson, ;), resolution improvement in other conventional optical techniques such as reflection and other modalities are constantly attempted (Ploem, ; Brakenhoff et al ., ; Koerten et al ., ; ; Cox et al ., ; Cox et al ., ; Brakenhoff et al ., ; Cornelesetenvelde et al ., ; Prins et al ., ; Brakenhoff & Muller, ; Prins et al ., ; Azeredo et al ., ; Ploem & Prins, ; Sivaguru et al ., ; Sivaguru et al ., ). Superresolution techniques such as stimulated emission and depletion (Hell & Wichmann, ), structured illumination (Gustafsson, ), Airyscan (Sheppard, ; Huff, ) and PALM/STORM (Betzig et al ., ) have recently been commercialised to go beyond diffraction limit of resolution in biological samples labelled with fluorescent targets.…”
Section: Introductionmentioning
confidence: 97%
“…Sivaguru et al evaluated the evolution of calcium oxalate stones using geobiology [1]. They observed how calcium oxalate stones undergo multiple events of dissolution during crystallization and growth in the kidney based on super-resolution auto-fluorescence images.…”
mentioning
confidence: 99%